Case Flow Management : Key Principles and the Systems to Support Them - Gramckow, Heike P.; Nussenblatt, Valerie (World Bank, Washington, DC, 2014)
It has become increasingly clear that courts across the globe must do more to better organize and manage their caseload and that automation alone is not the answer. In response to this need, case flow management has emerged to become the central method of promoting greater court responsibility and accountability for efficient case processing. For over thirty years court case management concepts have evolved, starting in the United States (U.S.), spreading to other industrialized common law countries initially. Yet, for many judicial systems, the concept, techniques, and supporting systems of case flow management are still relatively new ideas that need to be more fully understood. This paper helps develop a basic understanding of case flow management by defining the concept, outlining the various techniques used, presenting in general the different case management information systems that support those techniques, and outlining the core steps a judicial system can take to plan for, select, and implement case management software. The aim is to provide an introduction for assisting judiciaries in developing a case flow management approach that works best in their own environment. This paper is organized as follows: chapter one gives introduction; chapter two answers the question to what is case flow management within a court environment?; chapter three answers what are case management information systems?; chapter four focuses on planning for, selecting, and implementing new case management software; and chapter five gives conclusions.